PMM.88 Screening for Down's Syndrome in Women with Renal Disease. (9th June 2014) - Sarween, N; Mills, I; Day, C; Lipkin, G; Knox, E
Abstract : Introduction: In 2001, the UK National Screening Committee advised that all pregnant mothers should be offered a screening test for Down's syndrome (DS). This is performed at first (biomarkers and ultrasound) or second trimester (biochemical screen). There are limited data reporting pregnant women with chronic kidney disease (CKD) have higher false positive screening rates possibly because of reduced clearance of β-hCG (1–3). Our aim was to establish whether standard DS screening is appropriate in pregnant women with renal disease. Methods: We performed a retrospective, single centre review of DS screening data for women attending a tertiary renal-antenatal clinic over the past 5 years and correlated with clinical outcome. Results: A total of 240 women had renal function checked at the time of screening. Twenty-seven% had creatinine ≥60 µmol/L-above upper normal pregnancy value (range 24–544). There were a higher proportion of positive screens compared to the general population at first (5.7% vs 2%) and second trimester (9% vs 3.5%). No patient had a baby affected with DS. Increased creatinine was associated with higher levels of unconjugated oestriol (uE3), free and total β-hCG (p ≤ 0.01) and a higher DS risk score (p ≤ 0.01). Increased proteinuria also correlated with a higher β-hCG (p ≤ 0.01) and risk score (p ≤ 0.02). In patients with a high risk score; 30% had IUGR, 10% pre-term delivery and 56% delivered a small baby. Conclusion: Renal function appears to affect levels of β-hCG and uE3and also independently influence the risk score in DS screening. Alternative screening may need to be considered in this group or renal impairment corrected for. References: Cararach V, Casals E, Martinez S, Carmona F, Aibar C, Quinto LI, et al . Abnormal renal function as a cause of false-positive biochemical screening for Down's syndrome. Lancet. 1997;350(9087):1295. Epub 1997/11/14 Cheng PJ, Liu CM, Chang SD, Lin YT, Soong YK. Elevated second-trimester maternal serum hCG in patients undergoing haemodialysis. Prenat Diagn. 1999;19(10):955–8. Epub 1999/10/16 Benachi A, Dreux S, Kaddioui-Maalej S, Czerkiewicz I, Fakhouri F, Thervet E, et al . Down syndrome maternal serum screening in patients with renal disease. Am J Obstet Gynecol. 2010;203(1):60 e1–4. Epub 2010/04/27